2016
DOI: 10.32677/ijch.2016.v03.i01.007
|View full text |Cite
|
Sign up to set email alerts
|

A study of prevalence of Mycoplasma pneumoniae pneumonia and validation of Immunoglobulin M for Mycoplasma pneumoniae in the diagnosis of Mycoplasma pneumoniae pneumonia

Abstract: Background: Mycoplasma pneumoniae pneumonia (MPP) is one of the most common causes of childhood community-acquired pneumonia (CAP) and common cause of mortality and morbidity in young children. Polymerase chain reaction (PCR) is promising with higher specificity and superior sensitivity to that of culture or single point serology. Objective: This study was conducted to estimate the prevalence of MPP, and to compare the efficacy of PCR and immunoglobulin M (IgM) enzyme-linked immunosorbent assay (ELISA) for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…About 90.32% cases belonged to age group <5 years and this age group also had a maximum number of positive cases which is in agreement with the epidemiological data based on serological studies [4,13]. Comparison of clinical signs and symptoms between M. pneumoniae-infected and non-infected patients revealed that fever, cough, hurried breathing, with signs of crepitations, intercostal and subcostal retractions were predominant findings in M. pneumoniae-positive patients (Table 1) and are comparable with findings of Chaudhry R et al, [14] Using a combination of PCR and serology, overall 31 of 133 patients included in the present study (23.3%) were found positive and the results are comparable with prevalence rate of 10-30% reported in different studies [14][15][16]. In the present study, maximum samples were positive by serology followed by PCR.…”
Section: Discussionsupporting
confidence: 91%
“…About 90.32% cases belonged to age group <5 years and this age group also had a maximum number of positive cases which is in agreement with the epidemiological data based on serological studies [4,13]. Comparison of clinical signs and symptoms between M. pneumoniae-infected and non-infected patients revealed that fever, cough, hurried breathing, with signs of crepitations, intercostal and subcostal retractions were predominant findings in M. pneumoniae-positive patients (Table 1) and are comparable with findings of Chaudhry R et al, [14] Using a combination of PCR and serology, overall 31 of 133 patients included in the present study (23.3%) were found positive and the results are comparable with prevalence rate of 10-30% reported in different studies [14][15][16]. In the present study, maximum samples were positive by serology followed by PCR.…”
Section: Discussionsupporting
confidence: 91%